GAMBARAN KADAR HEMOGLOBIN DAN INDEKS ERITROSIT SEBAGAI PENANDA ANEMIA PADA KARYAWAN PT. ANTAM DI KECAMATAN POMALAA KABUPATEN KOLAKA PROVINSI SULAWESI TENGGARA - Balaka, Kemal Idris; Umar, Heni; Saadi, Niar Jumiarti (Jurnal Analis Kesehatan Kendari, 2023)
ABSTRACT Anemia is a condition in which the hemoglobin (Hb) level in the blood is less than normal. Anemia is a nutritional problem that is widely found throughout the world that not only occurs in developing countries but also in developed countries Anemia is a condition with hemoglobin levels, hematocrit and red blood cells that are lower than normal values. Hemoglobin functions to deliver oxygen throughout the body and gives color to erythrocyte cells. In addition to hemoglobin the supporting parameters for knowing someone suffering from anemia is to look at the erythrocyte index. The purpose of this study was to determine the description of hemoglobin levels and erythrocyte index as an anemic marker in employees of PT. Antam in Pomalaa District, Kolaka Regency, Southeast Sulawesi Province. This type of is descriptive to determine the description of hemoglobin levels and erythrocyte index as a marker of anemia in employees of PT. Antam where the number of samples was 25 people with the hemotology analyzer method and purposive sampling technique. Based on the research results of research conducted on 25 samples of hemoglobin levels and erythrocyte index as markers of anemia in employees of PT. Antam in Pomalaa District, Kolaka Regency, Southeast Sulawesi Province, obtained normal hemoglonin and erythrocyte index (100%). Keywords: Anemia, Hemoglobin, Erythrocyte Index, Employees PT. Antam ABSTRAK Anemia adalah suatu keadaan dimana kadar Hemoglobin (Hb) dalam darah kurang dari normal. Anemia merupakan masalah gizi yang banyak terdapat di seluruh dunia yang tidak hanya terjadi di negara berkembang tetapi juga di negara maju Anemia adalah keadaan dengan kadar hemoglobin, hematokrit dan sel darah merah yang lebih rendah dari nilai normal. Hemoglobin berfungsi mengantarkan oksigen keseluruh tubuh dan memberi warna pada sel eritrosit. Selain hemoglobin parameter penunjang untuk mengetahui seseorang menderita anemia adalah dengan melihat indeks eritrosit. Tujuan penelitian ini untuk mengetahui gambaran kadar hemoglobin dan indeks eritrosit sebagai penanda anemia pada karyawan PT.Antam di Kecamatan Pomalaa Kabupaten Kolaka Provinsi Sulawesi Tenggara. Jenis penelitian adalah deskriptif untuk mengetahui gambaran kadar hemoglobin dan indeks eritrosit sebagai penanda anemia pada karyawan PT. Antam dimana jumlah sampel sebanyak 25 orang dengan metode hemotology analyzer dan teknik pengambilan sampel purposive sampling. Berdasarkan hasil penelitan yang telah dilakukan terhadap 25 sampel kadar hemoglobin dan indeks eritrosit sebagai penanda anemia pada karyawan PT.Antam di Kecamatan Pomalaa Kabupaten Kolaka Provinsi Sulawesi Tenggara diperoleh nilai kadar hemoglobin dan indeks eritrosit normal (100%). Kata kunci: Anemia, Hemoglobin, Indeks Eritrosit, Karyawan PT. Antam